Unravelling The Loan-growth Nexus: A Technology Intensity Based Analysis - Büşra Şimşek; Halil Tunalı (İktisat Politikası Araştırmaları Dergisi)
This study examines the relationship between short and medium-long-term loans used by the manufacturing industry sectors in Turkey, classified by their technology intensities, and the industrial production index for each technology intensity. The analysis employs monthly data from 2005 to 2022. This study differs from other studies in the literature by classifying manufacturing industry sectors according to their technology intensities and examining the effects of short- and medium-long-term loans on the sectoral industrial index in line with this classification, using multidimensional homogeneous and heterogeneous panel data methods. The empirical findings indicate that both short and medium-long-term loans have a significant positive effect on the industrial production index across all technology levels for the entire panel. The results based on the technology intensity classification indicate that in the high-tech sectors, short-term loans have a stronger positive impact on the industrial production index than medium- to long-term loans. For medium-high technology sectors, medium-long-term loans have a greater positive effect. Similarly, medium-long-term loans show a stronger positive impact on the medium-low and low technology sectors compared to short-term loans.